PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi pada Perusahaan Pertambangan di Bursa Efek Indonesia Tahun 2015 – 2018) - Betrinasih Aldina; Suprihatmi Sri Wardiningsih; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research was conducted to explain the effect of company size, leverage and profitability on the disclosure of corporate social responsibility on mining companies listed on the Indonesian stock exchange in 2015 – 2018. CSR disclosure can be seen in the social responsibility report contained in the mining company's annual report. This study uses a population of 49 mining companies listed on the Indonesia Stock Exchange in 2015 – 2018. Samples were selected using a purposive sampling technique and obtained 11 companies that met the sample criteria. The analysis technique used in this study is the classic assumption test, multiple linear regression test, and hypothesis testing. The results of this study indicate that partially company size has a significant effect while leverage and profitability do not significantly influence the disclosure of corporate social responsibility. Simultaneously, company size, leverage and profitability have a significant influence on the disclosure of corporate social responsibility on mining companies listed on the Indonesia Stock Exchange in 2015 – 2018.